2021
DOI: 10.1002/pmh.1533
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personality disorders and personality traits on psychotherapy treatment outcome of eating disorders: A systematic review

Abstract: A significant proportion of those with eating disorders (EDs) do not respond to first‐line treatments. This systematic review was conducted to identify whether personality disorders (PDs)/traits predict or moderate ED treatment outcomes and whether these outcomes were differentially influenced by ED or PD diagnostic subtypes, or treatment approach. A comprehensive systematic literature search was conducted using the PRISMA guidelines. A total of seven randomised controlled trials (RCTs) plus four follow‐up stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…This is a recurring methodological challenge when studying the relationship between PD and ED. Comorbid PD is associated with complications to clinical care and could possibly represent barriers to recovery that should be addressed in therapy (Simpson et al, 2021) in mind, BMI was controlled for in the MLM analyses, and it did not seem to significantly impact the ED-PD comorbidity. Regardless of this, we cannot exclude the possibility that the occurrence of PD would differ had the patients achieved normal weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a recurring methodological challenge when studying the relationship between PD and ED. Comorbid PD is associated with complications to clinical care and could possibly represent barriers to recovery that should be addressed in therapy (Simpson et al, 2021) in mind, BMI was controlled for in the MLM analyses, and it did not seem to significantly impact the ED-PD comorbidity. Regardless of this, we cannot exclude the possibility that the occurrence of PD would differ had the patients achieved normal weight.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid PD in patients with ED are associated with increased levels of general psychopathology despite high treatment utilization (Cassin & von Ranson, 2005 ; Keel et al, 2002 ; Voderholzer et al, 2021 ; Zeeck et al, 2007 ), making this a matter of clinical importance. A recent systematic review (Simpson et al, 2021 ) revealed mostly unfavorable treatment outcomes for ED, possibly because ED symptoms tend to become more severe and intractable when occurring alongside a PD. The comorbidity of PD and ED may initiate self‐reinforcing feedback, exacerbating the role of ED symptoms as dysfunctional affect regulating and coping strategies (Helverskov et al, 2010 ; Sansone & Sansone, 2010 ; Simpson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps most prominently, the novel ICD-11 personality disorder model takes a dimensional and trait-based approach, comprising general personality dysfunction and five more specific personality trait domains [ 8 , 9 ]. Although the ICD-11 will be used in clinical practice worldwide and despite the importance of personality for case formulations and personalized treatment of eating disorders [ 4 , 10 ], the relation of the ICD-11 personality disorder with eating pathology is, to date, unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Personality is crucial for the onset, course, and treatment of eating pathology (for reviews, see [1][2][3][4]. Much of the previous research into the personality-eating pathology association has used categorical conceptualizations (i.e., presence vs. absence of an eating or personality disorder; e.g., [5]).…”
Section: Introductionmentioning
confidence: 99%